Hardness and microstructure characterization of hardfacing alloys deposited by the shielded metal arc welding (SMAW) on AISI 1045 medium carbon steel - Basyirun, Basyirun; Muhammad Hasnan, Habib; Deni Fajar Fitriyana, .; Muhammad Irfan, Nuryanta; Siregar, Januar Parlaungan; Cionita, Tezara; Da Silva Guterres, Natalino Fonseca; De Sousa Da Silva, Mateus (Penerbit UTHM, 2024)
A ring frame is a machine used for yarn production in the textile industry. Continuous use of the machine results in wear on the shaft timing pulley on the ring frame machine. To improve this condition, repairs are needed, one of which uses the hardfacing method. This study aims to determine the effect of hardfacing on the microstructure and hardness of the shaft timing pulley made from AISI 1045. The hardfacing process used the shielded metal arc welding (SMAW) method with welding current variations of 115 A, 125 A, 135 A, 145 A, and 155 A. In this study, the electrode used was AWS A5.1 E7018 with a diameter of 3.2 mm. The hardfacing product obtained was then finished with a lathe to produce a shaft with a final diameter of 30 mm. In this study, microstructure and hardness tests were carried out on specimens before and after finishing. The results of this study showed that an increase in current caused an increase in the number of pearlite phases in the weld metal and HAZ (heat-affected zone) areas. While in the base metal, the increase in current increased the number of ferrite phases. The highest hardness value was found in specimens that were hardfaced with a current of 145 A. However, the hardness of the hardfacing layer will decrease with the use of currents greater than 145 A. The hardness of the specimens with hardfacing treatment at a current of 145 A resulted in hardness in the weld metal, HAZ, and base metal of 225 HV, 209 HV, and 203 HV, respectively. After the finishing process, the weld metal, HAZ, and base metal in this specimen produced a hardness of 225 HV, 217 HV, and 208 HV, respectively.